Economic pigging cycles for low-throughput pipelines. (November 2018) - Xie, Ying; Chen, Diwen; Mai, Fangrui
Wax deposition occurs frequently in waxy crude oil pipelines when the level of flow decreases, and pigging is needed at regular intervals. An economic pigging model is established in accordance with the objective function based on the sum of thermal costs, power costs, and single piping costs. Thus, by compiling a program, the most economical pigging cycle will be determined. Furthermore, the calculation methods for hydraulic and thermal constraints are given. Taking the example of the distance between the central processing platform and the land terminal external piping line of the M-field cluster, the effects of different inlet temperatures, throughput, and remnant wax thicknesses on the economic pigging cycle will be analyzed. The results show that with an increase in the inlet temperature, the total costs of the pipeline operation increase, while the pigging cycle will prolong. As throughput increases, total costs will decrease, while the pigging cycle also extends. When throughput is fixed, a remnant wax thickness of 0.4 mm helps reduce the total operating costs of the pipeline at different inlet temperatures. While throughput varies, a remnant wax thickness from 0.2 to 0.4 mm can reduce total costs at a fixed inlet temperature.